Faktor Faktor yang Mempengaruhi Kinerja Guru dan Motivasi Kerja dari Gaya Kepemimpinan dan Lingkungan Sekolah Disalah Satu SMP Jakarta Pusat - Harsono, Harsono; Ali, Hapzi; Fauzi, Ahmad (Dinasti Review, 2023)
The purpose of this study was to determine the significant correlation of leadership style (X1), and school environment (X2) to teacher performance (Z) mediated by motivation (Y). The sample methodology is saturated with the Smart PLS 3.0 statistical test with results; 1) X1 has a significant effect on Y with a p-value of 0.000 with an outer loading value of 0.400. 2) X2 has a significant effect on Y with an outer loading value of 0.690. 3) X1 has a significant negative effect on Z with a p-value of 0.013, and an outer loading value of -0.289. 4) X2 has a significant negative effect on Z with a p-value of 0.025, and an outer loading value of -0.321. 5) Y has a significant effect on Z with a p-value of 0.000 and an outer loading value of 0.926. As for the indirect hypothesis 6) (X1) the p-Value obtained is 0.000 and the outer loading value is 0.371/37.1% and 7) (X2) the p-Value is 0.000 and the outer loading value is 0.639/63.9%. All hypotheses have a significant positive effect because all of them fulfill the p-value <0.05. The outer loading value of 63.9% means that the school environment is significant > X1. Its meaning must be improved such as infrastructure, communication relations, etc. The final result of the Independent Variable has a significant positive influence and a strong correlation to the dependent variable.